Interaction of Escherichia coli heat-labile enterotoxin B-pentamer with exopolysaccharides from Leuconostoc mesenteroides P35: Insights from surface plasmon resonance and molecular docking studies. (December 2022) - Azari-Anpar, Mojtaba; Degraeve, Pascal; Oulahal, Nadia; Adt, Isabelle; Jahanbin, Kambiz; Demarigny, Yann; Assifaoui, Ali; Tabatabaei Yazdi, Farideh
Abstract: In this study, the interaction of exopolysaccharides from Leuconostoc mesenteroides P35 (EPS-LM) with Escherichia coli heat-labile enterotoxin B-pentamer (LTB) was investigated at different concentrations and temperatures by using surface plasmon resonance (SPR) and molecular docking approaches. FT-IR spectral analysis together with HPTLC analysis revealing that glucose is the only constitutive monosaccharide of EPS-LM suggests that its structure is composed of dextran with α-D (1 → 6) glycosidic linkages. SPR analysis revealed the high affinity of EPS-LM for immobilized LTB toxin (KA =(2.05 ± 0.04) × 10 6 mol.L −1 at 37°C). The binding process was spontaneous (ΔG<0), endothermic (ΔH>0), and entropy-driven (ΔS>0) with an increase of KA with temperature. This suggests that EPS-LM - LTB interaction is dominated by hydrophobic forces. The binding affinity of EPS-LM to LTB had negligible dependence on enthalpy (ΔH = 0.084 kJ mol −1 ). Further, molecular docking results suggested the presence of some binding sites of EPS-LM on the LTB through hydrophobic forces (Lys, Asp, Arg, Glu) and also hydrogen bonding (Glu) in the hydrophobic core of LTB. Besides autodock studies, Schiffer-Edmundson helical wheel diagrams of LTB in α-helix domain suggested that LTB hydrophobic core is a highly effective region, which was able to form favorable non-polar interactions of the protein's binding surface (with amino acids residues such as Tyr, Leu, Ile) with EPS-LM. This study provided thus further insights into the interactions between EPS-LM and LTB, suggesting that EPS produced by some LAB, such as EPS produced by Ln. mesenteroides P35 strain are good candidates to inhibit E. coli toxin activity. Highlights: E. coli heat-labile enterotoxin B-pentamer was immobilized on a surface sensor. Ln. mesenteroides P35 exopolysaccharides had a high affinity for E. coli enterotoxin. Thermodynamic analysis of binding suggests a dominant contribution of hydrophobic forces. Molecular docking suggests putative binding sites along E. coli enterotoxin sequence.